2019
DOI: 10.1111/jnc.14818
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic acid‐derived metabolites constitute the majority of oxylipins in the rat pup brain and stimulate axonal growth in primary rat cortical neuron‐glia co‐cultures in a sex‐dependent manner

Abstract: In adult rats, omega-6 linoleic acid (LA, serves as a precursor to oxidized LA metabolites (OXLAMs) known to regulate multiple signaling processes in the brain. However, little is known regarding the levels or role(s) of LA and its metabolites during brain development. To address this gap, fatty acids within various brain lipid pools, and their oxidized metabolites (oxylipins) were quantified in brains from 1-day-old male and female pups using gas chromatography and liquid chromatography coupled to tandem mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…release and reesterification) of free oxylipins (Otoki et al, 2020). Free oxylipins are more bioactive than esterified oxylipins (Lahvic et al, 2018;Obinata et al, 2005), consistent with studies showing that they act as signaling molecules (Hennebelle et al, 2019). Thus, understanding their localization and proportional distribution relative to esterified pools in human milk would inform on how milk serves as a signaling system in infants.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…release and reesterification) of free oxylipins (Otoki et al, 2020). Free oxylipins are more bioactive than esterified oxylipins (Lahvic et al, 2018;Obinata et al, 2005), consistent with studies showing that they act as signaling molecules (Hennebelle et al, 2019). Thus, understanding their localization and proportional distribution relative to esterified pools in human milk would inform on how milk serves as a signaling system in infants.…”
Section: Introductionsupporting
confidence: 73%
“…Little is known about the role of variations in breast milk LNA or its oxidized metabolites on infant development. A recent study found that LNA and its metabolite, 13‐HODE, increased axonal outgrowth in female and male cortical neurons of rat pups, respectively (Hennebelle et al, 2019). LNA‐derived oxylipins accounted for approximately 50% of detected oxylipins in the brains of 1‐day‐old pups, although it is not known whether excess LNA in breast milk would further increase these levels during lactation (Hennebelle et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…peroxide content) and that various heat treatment conditions would alter oxylipins and provide new insight into the specific oxidized fatty acid species that are formed during processing. The latter is of particular importance for infant nutrition when considering the role of oxylipins in key aspects of development [20].…”
Section: Introductionmentioning
confidence: 99%
“…Produced by endothelial cells, it would behave like an anti-inflammatory metabolite as a ligand for PPAR α and γ. Its synthesis led to reduce angiogenesis in colon and prostate cancer 44 or enhanced the axonal outgrowth in primary cortical neurons during development of rats in a gender-dependent manner 45 . Altogether, these works underline the pleiotropic dimension of action of HODEs.…”
Section: Discussionmentioning
confidence: 99%